2020
DOI: 10.3389/fbioe.2020.00946
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Inhibits High-Density Cell Sheet Culture Induced Mesenchymal Stromal Cell Aging by Targeting Cell Cycle Inhibitor p27

Abstract: Mesenchymal stromal cell senescence and apoptosis have been identified as critical molecular hallmarks in aging. In this study, we used stromal cell sheet culture as an in vitro model to study the progressive changes of cellular senescence, apoptosis and underlying mechanism in Wnt3a treated cells. Our results showed fresh bone marrow mesenchymal stromal cells (BMSCs) become senescent and undergo apoptosis with increased inflammatory profile and Reactive Oxygen Species (ROS) in high-density cell sheet cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Wnt Our studies indicate that the primary role of Wnt is to promote cell cycle progression, aligning with previous studies in cell culture where Wnt signaling induces cyclin D1 expression via ErbB1, promoting the transition from G1 to S phase [70, 71], and represses the cell cycle inhibitor p27 [72]. However, our results show no indicate no discernible change on the balance between proliferative and differentiative divisions following Wnt inhibition, contrary to other studies that link Wnt signaling with differentiation [33, 34, 32].…”
Section: Discussionsupporting
confidence: 89%
“…Wnt Our studies indicate that the primary role of Wnt is to promote cell cycle progression, aligning with previous studies in cell culture where Wnt signaling induces cyclin D1 expression via ErbB1, promoting the transition from G1 to S phase [70, 71], and represses the cell cycle inhibitor p27 [72]. However, our results show no indicate no discernible change on the balance between proliferative and differentiative divisions following Wnt inhibition, contrary to other studies that link Wnt signaling with differentiation [33, 34, 32].…”
Section: Discussionsupporting
confidence: 89%
“…Co-treatment of cells with WNT3a and WNT5a revealed that the non-standard ligand WNT5a reduces the ability of WNT3a to induce cellular senescence ( 64 ). Treatment of cells with WNT3a increases the expression of cell cycle inhibitors p16, p21, and p53, but decreased the expression of p27 ( 71 ). Moreover, p27 can block the cell cycle transition from G1 to S phase, thereby inducing cell quiescence ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great promise of MSC sheets, one major challenge is that they undergo rapid senescence in as early as 3 days in high-confluency culture [ 11 , 12 ]. There is a critical need for techniques to prolong the function of these MSCs and optimize their treatment capacity.…”
Section: Introductionmentioning
confidence: 99%
“…There is a critical need for techniques to prolong the function of these MSCs and optimize their treatment capacity. MSCs within high-confluency culture acquire the hallmarks of aging, such as the absence of proliferative markers, increased senescence-associated β-galactosidase (SA β-GAL) activity, expression of the senescence-associated secretory phenotype (SASP), and expression of cell cycle inhibitors [ 11 ]. For many therapeutic applications, especially with transplantations for bone regeneration applications, these MSC sheets must be grown in culture for several days, or weeks, before transplantation.…”
Section: Introductionmentioning
confidence: 99%